채엽 효율 및 수량성이 높은 엽용 들깨 신품종 ‘동글1호’ - 이명희(Myoung-Hee Lee); 정찬식(Chan-Sik Jung); 배석복(Suk-Bok Pae); 오기원(Ki-Won Oh); 이유영(Yu-Young Lee); 오세관(Se-Kwan Oh); 박금룡(Keum-Yong Park); 안영섭(Young-Seob Ahn); 박충범(Chung-Beom Park) (Korean journal of breeding, 2012)
‘동글1호’는 잎수확을 목적으로 하는 품종육성을 위하여 잎들깨1호와 차조기 유전자원 YCPL199을 인공교배하여 계통육종법으로 선발한 YPL17-2B-18-4-4-10-7-1 계통이다. ‘동글1호’의 특징으로 잎모양은 둥근 심장형이며 잎색은 뒷면 자주색 발현이 양호하다. 또한 경색은 녹색, 화색은 흰색이고 종자는 암갈색의 구형이다. 채엽재배시 ‘동글1호’의 일반특성은 ‘잎들깨1호’와 비교하여 최대엽장은 16.2 cm로 비교적 작은 편이며 상품잎당 속잎비율(68.7%)이 높아 동계 수확 작업이 용이하다. ‘동글1호’는 2년간 하계노지재배에서 종실수량은 82 kg/10a였고, 동계시설재배에서 상품잎수가 4,350 천매/10a로 ‘잎들깨1호’에 비해 많았으며 잎무게는 5,798 kg/10a 비슷하였다. ‘Donggeul1’ is a new leaf vegetable perilla (Perilla frutescens (L.) Britton) variety developed from a cross between Ipdeulkkae1 and YCPL199 at the Department of Functional Crop, National Institute of Crop Science, Rural Development Administration, in 2006. For the cultivation of leaf vegetable perilla, the plants were grown with a spacing of 7×7 cm between rows and plants and all branches were removed to harvest uniform leaves from main stem, because the amount of the next harvesting leaf an important characteristic for the growth of the plant. ‘Donggeul1’ grows vigorously and produce high quality leaves with higher amount of the next harvesting leaves compared to a check cultivar, ‘Ipdeulkkae1’. For the leaf production, ‘Donggeul1’ is adaptable to whole arable land in South Korea. However, because of its late maturity, seed production reguires the rain sheltering stractares.